Interkulturel kommunikation og høflighed i anmodninger - Pilegaard, Morten (HERMES - Journal of Language and Communication in Business, 1989)
This paper deals with aspects of intercultural communication and presents the theoretical basis for a study of linguistic politeness in the realization of requests in English with the aim of analyzing requests in intercultural business correspondence (Danish/English). the hypothesis is that Danes corresponding to English are lacking in pragmalinguistic and sociopragmatic competence.